ENERGY REGULATION BY DIFFERENT MOLECULES - Dejanova, Beti; Petrovska, Sunchica; Pluncevikj Gligoroska, Jasmina; Manchevska, Sanja; Spirkoska Vangelovska, Biljana; Nestorova, Mihaela (Faculty of Physical Education, Sport and Health, Skopje, Republic of Macedonia, 2022)
Abstract Energy homeostasis is regulated by several physiological systems such as endocrine, gastrointestinal, and nervous system, that contribute to maintaining the balance between energy expenditure and energy intake. Food intake as well as food utilization are essential components in the maintenance of energy balance. Exercise is a state that interferes with energy regulation, thus it has a good impact on healthy lifestyle and long lifespan. The aim of the study was to discover the possible role of some energy regulation molecules and their influence during exercise. A number of 37 scientific studies from PubMed, ScienceDirect, MEDLINE, and Scopus databases were examined from the period of the last 20 years, combining the physiological mechanisms relatedto energy regulation molecules. The Cochrane database was used by dividing molecules into different groups: anorexigenic / orexigenic molecules, incretins, adipokines, and myokines, all related to energy regulation and exercise induced metabolic changes. Thus, variety of molecules derived from the adipose tissue (Leptin, Adiponectin, IL-6 – Interleukin-6, TNF-α – tumor necrosis factor α), from the muscle tissue (Irisin, Myostatin), from intestine and gastric cells (YY - pancreatic peptide YY, GLP-1- Glucagon like peptide-1, GIP- Gastric inhibitory peptide, Ghrelin), from liver tissue (FGF-21- Fibroblast growth factor-21), from pancreatic cells (Amylin), and other molecules are being explored. To understand the exercise induced molecule action mechanisms and their interference, may be useful toward new pharmaceutical approaches, related to energy metabolism regulation. Key words: energy homeostasis; physiological mechanisms; exercise.
Keywords: energy homeostasis; physiological mechanisms; exercise